The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1103/physrevb.85.195429
|View full text |Cite
|
Sign up to set email alerts
|

Top and bottom interfaces in Fe-B multilayers investigated by Mössbauer spectroscopy

Abstract: Mössbauer spectroscopy is frequently applied to gain information on the interfaces in multilayers, and recently the layer sequence permutation of multitrilayers was suggested to enhance its capability to characterize bottom and top interfaces of a given layer. The sequence permutation, however, in the investigated Fe-BAg multitrilayers affected the waviness of the layers as well, and the results hinted at the possibility that although Ag does not mix with Fe and B, the Fe-B amorphous alloy formation is influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The application of this method is limited by the possible mixing and diffusion between the 57 Fe marker and the natural Fe layers, and in case of an extended interface, the quantitative conclusion is difficult. The use of an auxiliary layer prepared from an element non-mixing with iron, e.g., Ag, and the comparison of M/ 57 Fe/M and M/ 57 Fe/ Ag samples-where M can be any kind of material-was suggested recently 16 as a strategy to gain quantitative results on the difference between the top and the bottom Fe interface. The idea is very simple; if the top and the bottom interfaces are similar in an M/Fe/M trilayer, then the hyperfine parameters of the respective spectral component remain unaltered and the intensity of the interface sub-spectrum is halved when the top M layer is replaced by Ag.…”
Section: Introductionmentioning
confidence: 99%
“…The application of this method is limited by the possible mixing and diffusion between the 57 Fe marker and the natural Fe layers, and in case of an extended interface, the quantitative conclusion is difficult. The use of an auxiliary layer prepared from an element non-mixing with iron, e.g., Ag, and the comparison of M/ 57 Fe/M and M/ 57 Fe/ Ag samples-where M can be any kind of material-was suggested recently 16 as a strategy to gain quantitative results on the difference between the top and the bottom Fe interface. The idea is very simple; if the top and the bottom interfaces are similar in an M/Fe/M trilayer, then the hyperfine parameters of the respective spectral component remain unaltered and the intensity of the interface sub-spectrum is halved when the top M layer is replaced by Ag.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the sextet ascribed to the -Fe type phase continuously broadens as milling time increases due to the progressive formation of the supersaturated bcc Fe(Nb,B) solid solution and to a reduction of the crystal size, as will be described below. Fitting of complex spectra as those studied here is not free from ambiguities [3,33]. HFDs have been used for all the studied milling times.…”
Section: 3mentioning
confidence: 99%
“…Conversion Electron Mössbauer Spectroscopy (CEMS) has been used to study the magnetic properties of the Fe-superlattice systems at the monolayer level enhanced with the 57 Fe + Mössbauer isotopes [4,5,12,[14][15][16]. It was reported that Fe-layers of thickness ≤5 MLs were non-magnetic [5].…”
Section: Introductionmentioning
confidence: 99%